2003
DOI: 10.2174/0929867033457115
|View full text |Cite
|
Sign up to set email alerts
|

The Isoprostanes: Unique Products of Arachidonic Acid Oxidation-A Review

Abstract: The isoprostanes are a unique series of prostaglandin-like compounds formed in vivo from the free radical-catalyzed peroxidation of arachidonic acid independent of the cyclooxygenase enzyme. The purpose of this article is to summarize our knowledge regarding the isoprostanes and discuss what are avenues for future research. Novel aspects related to the biochemistry of isoprostane formation and methods by which these compounds are analyzed, including potential pitfalls that may occur during the analysis, are di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
146
0
6

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(161 citation statements)
references
References 112 publications
3
146
0
6
Order By: Relevance
“…12,13,23 Cerebrospinal fluid F2-isoprostanes are a unique series of prostaglandin-like compounds formed in vivo from the free radical-catalyzed peroxidation of arachidonic acid and have been used to assess peroxidation in patients with severe TBI. 3,4,17,35 Glycerol is an end product of phospholipid degradation in neural tissue cell membranes and is a marker of cell damage whether caused by O 2 toxicity via free radical formation and lipid peroxidation or secondarily from ischemia. 16,19,32 Levels of CSF F2-isoprostanes as well as microdialysate glycerol were significantly decreased following combined HBO 2 /NBH treatment.…”
Section: Oxygen Toxicitymentioning
confidence: 99%
“…12,13,23 Cerebrospinal fluid F2-isoprostanes are a unique series of prostaglandin-like compounds formed in vivo from the free radical-catalyzed peroxidation of arachidonic acid and have been used to assess peroxidation in patients with severe TBI. 3,4,17,35 Glycerol is an end product of phospholipid degradation in neural tissue cell membranes and is a marker of cell damage whether caused by O 2 toxicity via free radical formation and lipid peroxidation or secondarily from ischemia. 16,19,32 Levels of CSF F2-isoprostanes as well as microdialysate glycerol were significantly decreased following combined HBO 2 /NBH treatment.…”
Section: Oxygen Toxicitymentioning
confidence: 99%
“…These current findings from this study would suggest that Hcys could possibly be a potential reliable marker for cardiovascular risk. The results of in vivo studies have shown that rodent models of CAD in which hyperlipidaemia has been induced are associated with enhanced oxidative stress as reflected by the increased 8-isoprostane levels (Roberts and Morrow, 2000;Rokach et al, 1997;Famm and Morrow, 2003;Davi, Falco, Patrono, 2004). In our present study, plasma 8-isoprostane was found to be significantly higher in patients with FH and NFH compared to the control group which is in concordance with the results from other studies looking at the association between hypercholesterolaemia and levels of 8-isoprostane.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in two studies carried out in patients with NAFLD [60,61] , we found increased oxidative stress in vivo, by measuring urinary 8-iso-prostaglandin F2α (8-iso-PGF2α), which derives from the non-enzymatic oxidation of arachidonic acid [62] , and serum levels of soluble NOX2-derived peptide (sNOX2-dp), which is an indicator of NOX2 activation, a NADPH oxidase isoform involved in ROS generation [63,64] . In vivo measurement of 8-iso-PGF2α in urine is a validated and widely accepted reliable biomarker of oxidative stress in health and diseases [65] ; a recent study from our group demonstrated that 8-iso-PGF2α production is partly a result of activation of NOX2 [65] .…”
Section: Imtmentioning
confidence: 99%